2021
DOI: 10.1371/journal.ppat.1009356
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein N-linked glycans play a critical role in arenavirus pathogenicity

Abstract: Several arenaviruses cause hemorrhagic fevers in humans with high case fatality rates. A vaccine named Candid#1 is available only against Junin virus (JUNV) in Argentina. Specific N-linked glycans on the arenavirus surface glycoprotein (GP) mask important epitopes and help the virus evade antibody responses. However the role of GPC glycans in arenavirus pathogenicity is largely unclear. In a lethal animal model of hemorrhagic fever-causing Machupo virus (MACV) infection, we found that a chimeric MACV with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…6A). This is consistent with previous data demonstrating that MACV mutants lacking specific glycans on GPC are more susceptible to antibody neutralization 29 . We further performed ELISAs to measure the level of MACV GP1 and NP specific antibodies with purified MACV (Carvallo) GP1 and NP proteins.…”
Section: Macv-specific Humoral Response Is Generated After Immunization With Macv Gpcδn83/δn166/f438isupporting
confidence: 94%
See 4 more Smart Citations
“…6A). This is consistent with previous data demonstrating that MACV mutants lacking specific glycans on GPC are more susceptible to antibody neutralization 29 . We further performed ELISAs to measure the level of MACV GP1 and NP specific antibodies with purified MACV (Carvallo) GP1 and NP proteins.…”
Section: Macv-specific Humoral Response Is Generated After Immunization With Macv Gpcδn83/δn166/f438isupporting
confidence: 94%
“…In this study, we characterized MACV mutant containing the TMD F438I substitution and mutations at glycosylation sites on GP1. Our previous research revealed that neither the F438I substitution nor the glycosylation site mutations alone are sufficient for full attenuation in IFN-αβ/γ R -/mice 29,30 . This work demonstrates that the combination of the F438I substitution in TMD with the glycan deficiency at N83 and N166 of GPC led to full attenuation in our IFN-αβ/γ R -/mouse model.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations